2005
DOI: 10.12693/aphyspola.107.184
|View full text |Cite
|
Sign up to set email alerts
|

Broad Band THz Sensing by 2DEG Bow-Tie-Type Diodes

Abstract: We suggest a novel approach to detect broad band, 0.078-2.52 THz, electromagnetic radiation at room temperature using an asymmetrically--shaped bow-tie diode based on a modulation-doped GaAs/AlGaAs structure. We show that the voltage sensitivity in the range from 0.078 THz up to 0.8 THz has a plateau and its value is within 0.3-0.5 V/W. We consider the bow-tie diode design to increase the sensitivity of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…[50]; QCLs dataaccording to [10][11][12], [13][14][15][16][17], and [51]; plasma devices -emission from plasma waves in nanotransistors [31,32]; frequency -up to 5 THz. Solid state THz sensors: bow-tie diodes operating on hot carrier effects -according to [44][45][46]; TACIT -tunable antennacoupled intersubband terahertz -detector based on intraband transitions [52]; plasma devices -detection by plasma waves [24][25][26][27][28], frequency -up to 3.1 THz [35]; QCL structures as THz detectorsaccording to [19], THz QWIP -quantum well infrared photodetectors -operating on bound-to-continuum transitions [20,21] and [53]; HEIWIP -heterojunction interfacial workfunction internal photoemission -sensor [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50]; QCLs dataaccording to [10][11][12], [13][14][15][16][17], and [51]; plasma devices -emission from plasma waves in nanotransistors [31,32]; frequency -up to 5 THz. Solid state THz sensors: bow-tie diodes operating on hot carrier effects -according to [44][45][46]; TACIT -tunable antennacoupled intersubband terahertz -detector based on intraband transitions [52]; plasma devices -detection by plasma waves [24][25][26][27][28], frequency -up to 3.1 THz [35]; QCL structures as THz detectorsaccording to [19], THz QWIP -quantum well infrared photodetectors -operating on bound-to-continuum transitions [20,21] and [53]; HEIWIP -heterojunction interfacial workfunction internal photoemission -sensor [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…We have applied the same ideology like in the previous case, i. e. we have reduced the apex size down to 3-2 µm and modelled the device operation using the same two, the phenomenological and the FDTD, approaches. The results of voltage sensitivity of 2DEG bow ties with apexes of 12 and 3 µm [45] are given in Fig. 14.…”
Section: Deg Bow-tie Diodes Based On Gaas / Algaas Modulation-doped mentioning
confidence: 99%
“…However, in spite of progress made in hot-carrier detector technologies, the need for higher sensitivity still remains an issue for practical applications. Previous studies revealed that the sensitivity of the bow-tie device is determined mainly by the enhancement and concentration of the electric field in the vicinity of the apex [10,16]. Furthermore, it was discovered that narrowing of the diode apex leads to a greater electric field enhancement at the hot contact, which results in greater device sensitivity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The metalized leaf on the left concentrates the incident signal onto the mesa apex of the right leaf, which contains the 2DEG layer (Valušis et al, 2005). As discussed in Section 1.1, bigradient EMF together with n-n + TEMF occurs when a diode of such design is placed in a strong MW electric field.…”
Section: Electrical Properties Of Heterostructured Microwave Diodes W...mentioning
confidence: 99%
“…Investigation at higher frequencies up to 2.25 THz (Seliuta et al, 2004) showed that voltage sensitivity dropped by more than two orders of magnitude due to antenna effects that cause weaker coupling of incident radiation. In addition, it was determined (Valušis et al, 2005) that the width of the neck of the diode can influence detection properties as well. Diodes having 12 μm neck width showed voltage sensitivity up to 0.3 V/W, while 3 μm width diodes showed 0.5 V/W at 100 GHz.…”
Section: Electrical Properties Of Heterostructured Microwave Diodes W...mentioning
confidence: 99%